Mechanistic studies on δ-aminolevulinic acid uptake and efflux in a mammary adenocarcinoma cell line - Correa García, S. (2003)
δ-aminolevulinic acid (ALA) is the precursor in the biosynthesis of porphyrins. The knowledge of both the regulation of ALA entrance and efflux from the cells and the control of porphyrin biosynthesis is essential to improve ALA-mediated photodynamic therapy. In this work, we studied the regulation of ALA uptake and efflux by endogenously accumulated ALA and/or porphyrins in murine mammary adenocarcinoma cells. Under our set of conditions, the haem synthesis inhibitor succinyl acetone completely prevented porphobilinogen and porphyrin synthesis from ALA, and led to an increase in the intracellular ALA pool. However, neither intracellular ALA nor porphyrin pools regulate ALA uptake or efflux during the first 15 min of the process. Based on temperature dependence data, ALA but not γ-aminobutyric acid (GABA) efflux is mediated by a diffusion mechanism. Moreover, the addition of extracellular GABA not only did not influence the rate of ALA efflux but on the contrary it affected ALA uptake, showing the contribution of a saturable mechanism for the uptake, but not for the efflux of ALA from the cells. © 2003 Cancer Research UK.